Student Management Practices in a Leading Madrasah and Their Impact on Students’ Achievement at MAN 2 Kediri City - Era AuliyatulFaiza; Arifatul Mufitda; Yunia DwiLatifah (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
Student management is one of the key components in the education system that plays a strategic role in improving the quality and achievement of students. This study aims to analyze the implementation of student management in a leading madrasah to enhance student achievement at MAN 2 Kota Kediri. The research employed a qualitative descriptive approach with a case study method. Data were collected through observation, in-depth interviews, and documentation involving various stakeholders, including the Vice Principal for Student Affairs, Guidance and Counseling teachers, Akidah Akhlak subject teachers, competition coaches, and students with academic and non-academic achievements.The results reveal that MAN 2 Kota Kediri applies effective and sustainable student management strategies through strong collaboration among the school administration, teachers, and mentors. These strategies include a rigorous student admission process, systematic achievement development programs, and continuous motivation and facilitation to support student potential. The implementation of a conducive and well-structured student management system significantly contributes to the improvement of both academic and non-academic student achievements. Therefore, MAN 2 Kota Kediri is appropriately recognized as an outstanding madrasah and a model for effective student management implementation in Islamic educational institutions.